Evaluation of chemical disinfectants efficacy against escherichia coli biofilm developed at 37c on glass and stainless steel - Anas Muazu, A. Rahman Nor Iza, Umar Ahmed Faruk, Ogidi Jonathan Ajisafe, (Universiti Pendidikan Sultan Idris, 2016)
Evaluation of chemical disinfectants efficacy against escherichia coli biofilm developed at 37c on glass and stainless steel by Anas Muazu, A. Rahman Nor Iza, Umar Ahmed Faruk, Ogidi Jonathan Ajisafe,